Level of satisfaction and sexual and reproductive health needs of deaf persons in Ghana: a sequential explanatory mixed method study - Wisdom Kwadwo Mprah; Maxwell Peprah Opoku; Juventus Duorinaah; William Nketsia (BMC, 2022)
Abstract Background The intersection between deafness and culture in sub-Saharan African contexts such as Ghana has culminated in restricted access to sexual and reproductive health (SRH) services. While some attention has been given to the barriers faced by deaf persons in accessing SRH services, discussion of their needs and satisfaction with SRH services is at an embryonic stage. This lends support to the use of sequential mixed-method study design to assess the level of satisfaction and SRH needs of deaf persons. Methods This study was guided by explanatory sequential mixed-method study design. Thus, a two-phase data collection approach was adopted. In Phase I, a 32-item questionnaire with 16 items each for satisfaction regarding SRH services and SRH needs, was used for data collection from 288 deaf persons recruited from 3 of the 16 regions in Ghana. The data were subjected to the following computations: means, t-tests, analysis of variance, correlations, and multiple regression. In Phase II, a semi-structured interview guide was used to collect data from 60 participants who were drawn from the earlier pool. The interviews were subjected to thematic analysis. Results The results showed of correlation and multiple analyses showed a small relationship and significant contribution of needs in the variance of satisfaction. Also, there was a convergence between both the qualitative and quantitative data as participants confirmed the lack of consideration given to the needs of deaf persons regarding SRH service provisions. Conclusion Deaf persons who took part in this study were unsatisfied with SRH services due to barriers such as sign language interpreters and inaccessible information. Consequently, they expressed the need for preferred mode of communication and expedition of awareness creation on SRH. The study findings warrant the need for policymakers to inculcate the needs of deaf person in SRH services to improve access and thus, enhance satisfaction. For instance, recommendations such as the training of health professionals in the use of sign language could be considered in future SRH policy and other implications, are discussed.